Power of Attorney and Permission to Pledge an Estate Based on Tangerang District Court Stipulation No. 1155/Pdt.P/2021/PN.Tng - Amos Andi; Selamat Lumban Gaol; Sudarto Sudarto (JURNAL HUKUM SEHASEN, 2023)
The death of a person will cause problems with the property left behind, including how to continue or transfer the property left behind and who is entitled to receive / continue the property left behind, all of which are regulated by inheritance law. The summons (relaas) is one of the most important instruments in the court process. Without a summons the presence of the parties in court has no legal basis. A summons in civil procedure law is categorized as an authentic deed. Articles 165 HIR and 285 R.Bg and Article 1865 BW state that an authentic deed is a deed made before a public servant in the form prescribed by applicable law. Thus, everything contained in the relaas must be considered true, unless it can be proven otherwise. The purpose of this research consists of objective objectives and subjective objectives with benefits both theoretically and practically. The power of attorney and permission to pledge inherited property is one part of civil law as a whole and is part of family law. Inheritance law is closely related to the scope of human life, because every human being will definitely experience a legal event in the form of death. The legal consequences of the death of a person include the management and continuation of the rights and obligations of the deceased. Such is the case with the case studied in this paper, to pledge the estate of the deceased husband (children's share) a wife as a guardian of the child in marriage must make an application to the authorized Court, as stated in the Tangerang District Court Stipulation Number 1155/Pdt.P/2021/PN.TngThe act of Power of Attorney and Permission to pledge the estate should be done for the benefit of the child, namely to provide benefits and welfare for the child.